Religious Restrictions for Sports - Ahmad, Ibrahim Jalil Khalil (Journal of Islamic Sciences, 2021)
This thesis takes into consideration sports and specifies their religious restrictions. It also aims to provide people interested in sport with these religious restrictions which are illustrated through the descriptive and inductive approach. The thesis has arrived at the conclusion that sports are religiously permitted if they have met the religious conditions. In case a condition is missing, the permission turns into hatred or prohibition. The thesis also recommends that Olympic committees, sport federations and sport centers should have a verified book that is referred to in order to know the religious rules for sports. Also, it is recommended that sportsmen and coaches should attend an annual religious seminar to discuss sport and related issues.